PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP KINERJA KEUANGAN (Studi Kasus Pada Perusahaan Pertambangan Sub Sektor Batubara Yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Tax Planning and Deferred Tax Expense on Financial Performance in Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange. Taxes are one of the important sources of state revenue to finance state development. This study also discusses deferred tax and tax planning that will be carried out by the company in generating profits by looking at the financial performance of the company. The research period used is the 2016-2020 period). The type of research used in this research is quantitative with secondary data method. The variable for determining the sample of this study used purposive sampling method and based on the criteria obtained 40 company data and analyzed using panel data regression technique with random effects model to test the hypothesis. The dependent variable in this study is Financial Performance, while the independent variable in this study is Tax Planning and Deferred Tax Expense. Hypothesis testing in this study uses multiple linear regression using Eviews version 10 and Eviews version 12. The results of this study indicate that tax planning and deferred tax expense jointly affect the financial performance of the coal mining sub-sector listed on the Indonesia Stock Exchange in 2016 -2020.